2003
DOI: 10.1295/polymj.35.798
|View full text |Cite
|
Sign up to set email alerts
|

The Flory-Huggins Interaction Parameter and Thermoreversible Gelation of Poly(vinylidene fluoride) in Organic Solvents

Abstract: ABSTRACT:The Flory-Huggins interaction parameter (χ 12 ) between poly(vinylidene fluoride) (PVdF) and organic solvent was estimated experimentally over wide range of temperature by an inverse gas chromatography (IGC) using many kinds of solvents such as alkane, alkene, ketone, lactone, and nitrogen-containing solvent. The thermoreversible gelation of PVdF solution was discussed from the magnitude of interaction parameter χ 12 between PVdF and solvent. The parameter χ 12 was measured for a concentrated PVdF sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…To solve for M c , these equations require the polymer volume fraction of the swollen gel (V pol ), the molar volume of the solvent (V 0 ), the density of the polymer (r pol ), the Huggins solvent-polymer interaction parameter (m), the swelling factor (f) and the density of the solvent (r solv )-in this case cyclohexanone. Tazaki et al (2000) and Okabe et al (2003) have determined the Flory-Huggins interaction parameters (m) for PVDF homopolymer and a 12% HFP copolymer in cyclohexanone across a wide temperature range. Using their data, values of 0.3 and À0.3 were obtained for PVDF and 12% HFP copolymer, respectively.…”
Section: Sol-gel Analysismentioning
confidence: 99%
“…To solve for M c , these equations require the polymer volume fraction of the swollen gel (V pol ), the molar volume of the solvent (V 0 ), the density of the polymer (r pol ), the Huggins solvent-polymer interaction parameter (m), the swelling factor (f) and the density of the solvent (r solv )-in this case cyclohexanone. Tazaki et al (2000) and Okabe et al (2003) have determined the Flory-Huggins interaction parameters (m) for PVDF homopolymer and a 12% HFP copolymer in cyclohexanone across a wide temperature range. Using their data, values of 0.3 and À0.3 were obtained for PVDF and 12% HFP copolymer, respectively.…”
Section: Sol-gel Analysismentioning
confidence: 99%
“…27,28 We have also shown that T g m of poly(vinylidene fluoride) or poly(butylene succinate) gels increases with increasing 12 . 29,30 In view of these previous results, the junction size in sPS gels is thought to have a close relationship to the sPS-solvent interaction parameter though we have not measured 12 yet. That is to say, the size is presumed to become larger with increasing 12 .…”
Section: Junction Point Size Of Gelmentioning
confidence: 69%
“…A large difference in solubility parameters between PVdF and the gelation solvent would result in decreased swelling ratios, leading to an increase in T m g . We previously reported that the T m g values of PVdF gels in the absence of lithium salts 16 and those of poly(butylene succinate) gels 25 increase with an increase in the polymer-solvent interaction parameter. …”
Section: Gel-melting Temperaturementioning
confidence: 99%
“…[12][13][14][15] In addition, we experimentally estimated the Flory-Huggins interaction parameters (w 12 ) between PVdF and the organic solvents over a wide temperature range using inverse gas chromatography and then clarified the correlation between the thermoreversible gelation of a PVdF solution and the magnitude of w 12 . 16 Here, we report the results of a preliminary study of the gelation process and the structural morphology of a PVdF gel in the presence of a lithium salt, LiBF 4 . The morphology of the PVdF gel was studied by scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%